If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 2) + -4 = 0 Reorder the terms: 4(2 + 3x) + -4 = 0 (2 * 4 + 3x * 4) + -4 = 0 (8 + 12x) + -4 = 0 Reorder the terms: 8 + -4 + 12x = 0 Combine like terms: 8 + -4 = 4 4 + 12x = 0 Solving 4 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 12x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 12x = 0 + -4 12x = 0 + -4 Combine like terms: 0 + -4 = -4 12x = -4 Divide each side by '12'. x = -0.3333333333 Simplifying x = -0.3333333333
| x^3-3x^2-7x+a=0 | | 3x=25-y | | 5=4x-9+x-3x | | X-4=0.5X | | 100=2x-x+4x | | 1/2(18-5x)=1/3(6-4x) | | 3x-5y=-18 | | x+15+3=25+10 | | 16d=8 | | 12x-17-9=4 | | 9x+5-(3x+3)=32 | | 2x*34x= | | 10b-13b+20b= | | 85-2x=97-3x | | 12=(30*x)/(30+x) | | 2x+12=4x-50 | | 12=30*x/(30+x) | | 12=30*x/30+x | | 12=30*x/30*x | | (x-5)+(x-3)+x+(x+5)=29 | | 2a-b+3a+4b= | | 42x+51-17x+23=182+13x | | 3x^2+6x=2 | | 3(x+4)=16 | | 11x-25=5x+59 | | 3x+18x+15x+12x=144 | | 36+42x=120 | | 4x-6+14x-2=8x+4 | | 2x^2+7x=20 | | 7+42x=301 | | 18x+36=72 | | 5x+10=-5x+20 |